MODELLING THE MORBIDITY PATTERN OF TUBERCULOSIS AND ITS ASSOCIATED FACTORS IN OYO STATE, NIGERIA - Bidemi, Yusuf Oyindamola; Ayobami, Adepoju-Olajuwon Fatimah; Olamiposi, Owoeye Deborah; Abbas, Gbolahan (African Journal of Infectious Diseases (AJID), 2018)
Background: With the advent of HIV, the risk of Tuberculosis (TB) has increased. The trend in the number of cases of TBin Oyo state over the past five years has not been documented. Hence, this study reviewed the number of cases of TB anddetermined some of its associated factors.Materials and Methods: A retrospective analysis was conducted on TB surveillance data reported between January 1st2011 and December 31st 2014. Data were obtained from the integrated disease surveillance and response (IDSR) of Oyostate ministry of health, Nigeria. Number of TB cases, age, local government areas (LGA), month and year of reportingwas extracted. Data were analysed using descriptive statistics, negative binomial and the Poisson regression models. Modelfit was assessed using the AIC and the -2LogL.Results: The incidence of TB was highest in 2013 (23 per 10000 population) in Ibarapa East LGA. The risk ofTuberculosis was 62.8% higher in 2014 (IRR=1.628; 95%CI=1.281, 2.068) and also 17% higher in 2012 (IRR=1.170;95%CI=1.010, 1.356). Also, the risk of TB was highest in Ibarapa East LGA (IRR=2.576; 95%CI=1.945, 3.412) and lowestin Ogbomoso South LGA (IRR=0.229; 95%CI=0.069, 0.764). Adolescents and adults also had higher risk of TB comparedto children.Conclusion: The frequency of Tuberculosis declined overtime and older adults had a higher risk. The low frequency of TBin the state may be an indication and good evidence of concerted control measures. Efforts should be put in place to furtherbring down the number of cases especially in the identified hotspots.